2016
DOI: 10.1108/sajgbr-01-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, helping behavior and leaders’ effectiveness: a serial mediation model

Abstract: Purpose The purpose of this paper is to investigate the effect of leaders’ positive emotions on their followers’ perceptions of leaders’ effectiveness through a serial mediation mechanism that employed followers’ positive emotions and leaders’ helping behaviors as mediators. Design/methodology/approach This study is quantitative in nature. The data for it were collected from supervisors and subordinates in the restaurant and hotel industries of Pakistan. This study used a mix of convenient and purposive/judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Generally speaking, helping behavior, which includes acts of consideration, is promotive and cooperative in nature (Van Dyne and LePine, 1998). Previous research indicated that leaders' helping behavior did benefit in promoting leader effectiveness and relationship satisfaction (Asadullah et al, 2016;Hoption, 2016). In line with these studies, we argue that perceived leader's helping behavior has a positive effect on employees' thriving and can be explained from the following two perspectives.…”
Section: Theory and Hypotheses Perceived Leader's Helping Behavior Ansupporting
confidence: 73%
“…Generally speaking, helping behavior, which includes acts of consideration, is promotive and cooperative in nature (Van Dyne and LePine, 1998). Previous research indicated that leaders' helping behavior did benefit in promoting leader effectiveness and relationship satisfaction (Asadullah et al, 2016;Hoption, 2016). In line with these studies, we argue that perceived leader's helping behavior has a positive effect on employees' thriving and can be explained from the following two perspectives.…”
Section: Theory and Hypotheses Perceived Leader's Helping Behavior Ansupporting
confidence: 73%
“…In Asadullah et al. 's () survey of hospitality leader–follower dyads, leaders’ positive emotions were positively associated with followers’ positive emotions in the workplace, which mediated the relationship between leader positive emotions and leader effectiveness.…”
Section: Resultsmentioning
confidence: 97%
“…The body of extant research reviewed here collectively shows a significant relationship between a leader's emotions and followers’ emotions (Asadullah et al., ; Becker et al., ; Eberly & Fong, ). Specifically, the ability of the leader to influence the affective states of group members (the contagion ability) has typically been operationalized as a leader's emotion display and/or emotional expressions (e.g., Eberly & Fong, ; Visser et al., ), with only Cheng et al.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations